Síntese e análise estrutural de haletos de organilcalcogênios ( Se e Te ) com estados de oxidação mistos - Casagrande, Gleison Antonio (2007)
This work describes the synthesis and structural analysis of new organochalcogen halides with mixed oxidation states in the same molecule. Studies in the solid state by X-ray diffraction reveal a general tendency to associate the molecular entities via secondary bonds of the type E···X and X···X ( E = Se, Te; X = Br, I), to form different architectures, such as dimeric and supramolecular arrays. Studies in solution by 77Se and 125Te RMN spectroscopy reveal that the synthesized compounds present different behavior in solution than in the solid state. There is a general tendency for the cleavage of the secondary bonds present in the solid state with the formation of a dynamic equilibrium between the different species in solution.